Genetic analysis of three wild Eurasian eagle-owl subspecies, B. b. kiautschensis, B. b. ussuriensis, and B. b. tibetanus, in Chinese populations. Issue 3 (2nd July 2020) - Meng, Meng; Ma, Jianzhang; Laghari, Muhammad Younis; Ji, Jianwei
Abstract: The Eurasian eagle-owl ( Bubo bubo ) is distributed throughout Asia and Europe and contains approximately twelve subspecies. Three subspecies, B. b. kiautschensis, B. b. ussuriensi s, and B. b. tibetanus, are separately distributed in the refugia and plateau habitats of China. However, the genetics of these subspecies and populations have not been studied. Genetic differences were investigated among 32 individuals from six populations of these three B. bubo subspecies based on the mitochondrial genome. Low genetic diversity but high haplotype diversity was observed in these subspecies. The phylogenetic relationship of three B. bubo subspecies distributed in China was proven to be coordinated with geographic and environmental gradients. This study provides the first detailed insights into the mitochondrial genetic diversity of three Eurasian eagle-owl subspecies distributed in China and demonstrates the utility of the mitochondrial genome in intraspecific genetic population analyses of these eagle-owls.